IDEAL ENVIRONMENTAL RECOVERY MODEL FOR B3 ALUMINIUM SLAG WASTE IN JOMBANG - Arifin, Jainul (Universitas Airlangga, 2025)
The problem of B3 (hazardous and toxic) aluminium slag waste in Jombang Regency has persisted for over four decades, accumulating more than 100 million tons of hazardous residues on open land, agricultural fields, and riverbanks. This study employs a normative juridical method to examine national and regional legal frameworks, law enforcement practices, and judicial experiences in pollution cases, then formulates an ideal environmental recovery model for Jombang. The findings indicate that although Regional Regulation No. 8/2017 and Law No. 32/2009 provide a basis for remediation and recovery, implementation in the field remains hindered by limited institutional capacity, outdated industrial data, and low awareness among residents and business actors. The proposed recovery model includes: (1) formation of a “Aluminium Slag Recovery Task Force” comprising local government, Ministry of Environment and Forestry, Bappeda, Public Works Agency, small and medium aluminium industries (IKM), local cooperatives, and law enforcement; (2) execution of technical stages in accordance with Article 54 of Law No. 32/2009 (source cessation, remediation, rehabilitation, and restoration) using solidification/stabilization and phytoremediation techniques; (3) financing mechanisms based on the “polluter pays” and “strict liability” principles through environmental guarantee funds and incentives for compliant IKM; and (4) progressive law enforcement and capacity building of Jombang’s Environmental Office in monitoring, education, and public participation via a GIS dashboard and village‐level forums. Implementing this model is expected to accelerate ecosystem function recovery, generate economic value from properly treated slag, and ensure accountability and transparency in B3 waste management across Jombang.